Selecting a Turfgrass for Florida Lawns - Laurie E. Trenholm; J. Bryan Unruh; John L. Cisar (EDIS, 2008)
Revised! ENH-04, a 5-page fact sheet by L.E. Trenholm, J.B. Unruh, and J.L. Cisar, provides homeowners with guidelines in question format and a table to assist in selecting the right turfgrass variety for a home lawn. Published by the UF Department of Environmental Horticulture, November 2007.